Are Sleep Quality, Daytime Sleepiness and Depression Associated with Knee Pain? A Cross-Sectional Study in Older Adults - Kakazu, Viviane Akemi; Pinto, Rafael Z.; Dokkedal-Silva, Vinicius; Fernandes, Guilherme Luiz; Araujo, Cynthia Gobbi Alves; Pires, Gabriel Natan; Dias, Tayna A. [UNESP]; Tufik, Sergio; Andersen, Monica; Morelhao, Priscila K. (Thieme Medical Publ Inc, 2024)
Introduction Osteoarthritis (OA) is common among older adults, and studies have suggested that it is commonly associated with sleep problems and depression. However, the results are inconsistent concerning overall sleep quality, daytime sleepiness, and depression in studies that consider OA knee pain specifically. Objectives To examine the relationship between sleep quality, daytime sleepiness and depression, and OA knee pain in older adults. Methods This was a cross-sectional study. Adults aged 60 and above with OA knee pain according to the National Institute for Health and Care Excellence (NICE) guidelines, and who had preserved cognitive function were recruited. Sleep quality, daytime sleepiness, and depression symptoms were assessed using the Pittsburgh Sleep Quality Index (PSQI), the Epworth Sleepiness Scale (ESS), and the Center for Epidemiologic Studies Depression Scale (CESD), respectively. The generalized linear model (GzLM) approach was used in the statistical analysis. A logistic regression model was performed to evaluate whether ESS, PSQI, and CESD symptoms were associated with knee pain. Results The sample comprised 451 older adults. Sleep quality (OR = 1.22, 95% confidence interval [CI]: 1.07 to 1.40) and depressive symptoms (OR = 1.09, 95%CI: 1.01 to 1.17) were associated with knee pain, but there was no association with excessive daytime sleepiness (OR= 1.09, 95%CI: 0.90 to 1.20). Conclusions Sleep quality and depression symptoms are associated with knee pain.
Keywords: sleep; osteoarthritis; pain; older adults